O28 Experience of female genital mutilation (FGM) in a sexual health clinic. (8th June 2017) - Neill, Lorna; Dolan, Zac; Murphy, Siobhan; McSorley, John; Brook, Gary
Abstract : Introduction: After recommendations from the Intercollegiate Guidelines in 2013, our sexual health clinic introduced a diagnostic code and mandatory proforma to identify, record and report FGM. Methods: Retrospective case note review of all patients coded FGM. Results: All patients presenting were over 18. There were 210 FGM patients; 30/210 Type 1 (clitoridectomy); 40/210 Type 2 (excision); 35/210 Type 3 (infibulation); 79/210 Type 4; 26/210 unclassified. 71 had consensual FGM as adults; of whom 69 were Type 4 (typically genital piercing), 2 were Type 1. In FGM performed under 18 years old (139); average age of cutting was 6 years. Countries involved; Somalia 67% (93/139), Sierra Leone 7% (9/139), Eritrea, Nigeria and Ethiopia 4% (6/139) respectively. 14% (19/139) reported complications.12% (17/139) had prior reversal. 4% (6/139) expressed interest in reversal. 98% (136/139) knew FGM is illegal in the UK. There was no significant difference in the rates of bacterial STI's between both groups. Discussion: Our proforma assists in identifying and accurately recording information regarding FGM. No women required referral to police or social services. Some were signposted for surgical intervention. An increased incidence of pelvic pain was noted in those whose FGM was performed as children, with no reflected increase in bacterial STI's. An increased prevalence of blood borne viruses was also noted. Most women reported negative attitudes to FGM. Sexual health clinics are well placed to assist in awareness, risk assessment and education surrounding FGM.